2002
DOI: 10.1046/j.1462-2920.2002.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic genetic diversity throughout the salinity gradient of a coastal solar saltern

Abstract: Bacterial and archaeal assemblages have been studied in a multipond solar saltern using a range of microbial ecology techniques by four laboratories simultaneously. These include 16S rDNA sequencing from both denaturing gradient gel electrophoresis (DGGE) and clone libraries, and culturing methods. Water samples from eight ponds were analysed, covering a salinity range from near sea water (4% salt) to saturated sodium chloride (37% salt; ponds called crystallizers). Clone libraries focused on ponds with salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
244
7
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(296 citation statements)
references
References 49 publications
(27 reference statements)
34
244
7
5
Order By: Relevance
“…On the basis of these similarities, the microbial communities in the freshwater ponds exhibited typical freshwater bacterial groups as previously seen in other 16S rDNA surveys of freshwater environments (Arias et al, 2004;Lindstrom et al, 2005;Yannarell and Triplett, 2005;Briee et al, 2007). Corresponding analyses of microbiomes from the solar salterns showed the expected shift to an Archaea-dominated community in the high salinity pond (RodriguezValera et al, 1985;Benlloch et al, 2002). Archaea represented 2.2%, 38%, and 54% of the significant similarities in the low, medium, and high salinity salterns, respectively.…”
Section: Resultssupporting
confidence: 72%
“…On the basis of these similarities, the microbial communities in the freshwater ponds exhibited typical freshwater bacterial groups as previously seen in other 16S rDNA surveys of freshwater environments (Arias et al, 2004;Lindstrom et al, 2005;Yannarell and Triplett, 2005;Briee et al, 2007). Corresponding analyses of microbiomes from the solar salterns showed the expected shift to an Archaea-dominated community in the high salinity pond (RodriguezValera et al, 1985;Benlloch et al, 2002). Archaea represented 2.2%, 38%, and 54% of the significant similarities in the low, medium, and high salinity salterns, respectively.…”
Section: Resultssupporting
confidence: 72%
“…Salinity gradients are formed due to tidal flows and the evaporation of seawater in the intertidal regions of Hamelin Pool. These gradients result in the presence of microbial species adapted to different ranges of salinity and could result in a reduction in the diversity of bacterial and archaeal communities at higher salinities (Benlloch et al, 2002;Jungblut et al, 2005). High levels and fluctuations in salinity also result in an increase in biodiversity and favour the growth of halophilic microorganisms (Wieland and Kuhl, 2006;Abed et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, even though the reproducibility of this pattern is uncertain for microbial communities, several studies found evidence for a declining tendency in prokaryotic diversity along increasing salinity gradients (Benlloch et al, 2002;Hollister et al, 2010). Strikingly, both archaeal and bacterial diversity increased along with the salinity values from surface to the bottom of the Ursu Lake.…”
Section: Prokaryotic Diversitymentioning
confidence: 99%